The Use of Human Mesenchymal Stem Cells as Therapeutic Agents for the in vivo Treatment of Immune-Related Diseases: A Systematic Review - Leyendecker Jr., Alessander; Pinheiro, Carla Cristina Gomes; Amano, Mariane Tami; Bueno, Daniela Franco (Frontiers in Immunology, 2018)
Background: One of the greatest challenges for medicine is to find a safe and effective treatment for immune-related diseases. However, due to the low efficacy of the treatment available and the occurrence of serious adverse effects, many groups are currently searching for alternatives to the traditional therapy. In this regard, the use of human mesenchymal stem cells (hMSCs) represents a great promise for the treatment of a variety of immune-related diseases due to their potent immunomodulatory properties. The main objective of this study is, therefore, to present and summarize, through a systematic review of the literature, in vivo studies in which the efficacy of the administration of hMSCs for the treatment of immune-related diseases was evaluated. Methods: The article search was conducted in PubMed/MEDLINE, Scopus and Web of Science databases. Original research articles assessing the therapeutic potential of hMSCs administration for the in vivo treatment immune-related diseases, published from 1984 to December 2017, were selected and evaluated. Results: A total of 132 manuscripts formed the basis of this systematic review. Most of the studies analyzed reported positive results after hMSCs administration. Clinical effects commonly observed include an increase in the survival rates and a reduction in the severity and incidence of the immune-related diseases studied. In addition, hMSCs administration resulted in an inhibition in the proliferation and activation of CD19+ B cells, CD4+ Th1 and Th17 cells, CD8+ T cells, NK cells, macrophages, monocytes and neutrophils. The clonal expansion of both Bregs and Tregs cells, however, was stimulated. Administration of hMSCs also resulted in a reduction in the levels of pro-inflammatory cytokines such as IFN-γ, TNF-α, IL-1, IL-2, IL-12 and IL-17 and in an increase in the levels of immunoregulatory cytokines such as IL-4, IL-10 and IL-13. Conclusions: The results obtained in this study open new avenues for the treatment of immune-related diseases through the administration of hMSCs and emphasize the importance of the conduction of further studies in this area.